2011
DOI: 10.1242/jeb.055020
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric computed tomographic measurement of lung compression in seals and dolphins

Abstract: SUMMARY Lung compression of vertebrates as they dive poses anatomical and physiological challenges. There has been little direct observation of this. A harbor and a gray seal, a common dolphin and a harbor porpoise were each imaged post mortem under pressure using a radiolucent, fiberglass, water-filled pressure vessel rated to a depth equivalent of 170 m. The vessel was scanned using computed tomography (CT), and supported by a rail and counterweighted carriage magnetically linked to the CT tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 32 publications
4
67
0
Order By: Relevance
“…Differences in the exact depth of collapse in dives and chamber studies may be secondary to differences in the inhaled air volume under different conditions [3,4,7], to differences in heart rate and circulation time from the lungs to the location of the electrode in the aorta [16], or to limitations of the response time of the P O 2 electrode [17]. Approximately 75 per cent of the variation in depth of lung collapse in this study could be attributed to maximum depth of the dive, with lung collapse occurring at greater depths in deeper dives (figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the exact depth of collapse in dives and chamber studies may be secondary to differences in the inhaled air volume under different conditions [3,4,7], to differences in heart rate and circulation time from the lungs to the location of the electrode in the aorta [16], or to limitations of the response time of the P O 2 electrode [17]. Approximately 75 per cent of the variation in depth of lung collapse in this study could be attributed to maximum depth of the dive, with lung collapse occurring at greater depths in deeper dives (figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing thoracic pressure to ambient requires reducing the air volume in the thoracic cavity, but the degree to which this happens depends on the stiffness of the two parts of the thorax wall -the body wall and diaphragm. Cetacean body walls are stiff compared with those of pinnipeds (Leith, 1976;Moore et al, 2011), and van Nie argued they were too stiff to deform significantly at depth (van Nie, 1987), although this conflicts with evidence of inwards compression in odontocetes (Hui, 1975;Moore et al, 2011;Ridgway et al, 1969). Brown and Butler (Brown and Butler, 2000) proposed deformation of the diaphragm as the main mode of thorax cavity collapse, and Moore et al (Moore et al, 2011) suggested that the longitudinal orientation of the cetacean diaphragm could facilitate compression of the thoracic contents by the abdominal viscera.…”
Section: Discussionmentioning
confidence: 99%
“…Cetacean body walls are stiff compared with those of pinnipeds (Leith, 1976;Moore et al, 2011), and van Nie argued they were too stiff to deform significantly at depth (van Nie, 1987), although this conflicts with evidence of inwards compression in odontocetes (Hui, 1975;Moore et al, 2011;Ridgway et al, 1969). Brown and Butler (Brown and Butler, 2000) proposed deformation of the diaphragm as the main mode of thorax cavity collapse, and Moore et al (Moore et al, 2011) suggested that the longitudinal orientation of the cetacean diaphragm could facilitate compression of the thoracic contents by the abdominal viscera. The relative contributions of the body wall and diaphragm likely vary with depth, and at greater depths, where air-filled spaces are highly compressed, small discrepancies between actual and ideal air volumes can generate significant pressure gradients.…”
Section: Discussionmentioning
confidence: 99%
“…From measurements of nitrogen tension in the muscles of diving Tursiops, Ridgway and Howard showed that these animals may be vulnerable to decompression sickness at depths less than 70m, as they are not protected from circulating nitrogen via lung collapse (Ridgway and Howard, 1979). Measurements of lung collapse using computed tomography (CT) of carcasses (Moore et al, 2011) suggest that alveolar collapse in marine mammals may occur much deeper, such that diving mammals could be vulnerable to circulating nitrogen in a greater fraction of dives, especially in shallower parts of the water column (less than 100m). From these studies it is clear that there is considerable debate about the depth of lung collapse in diving Odontocetes, and comparisons of models of living animals with those of carcasses should be made with caution.…”
Section: Physiological and Biological Implications Of The Datamentioning
confidence: 99%